The design and implementation of vision-based autonomous rotorcraft landing - De Jager, Andries Matthys (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.